Health risk assessment of exposure to iron in gravity feed system water among indigenous people - Mohd Hanafi, Nurul Ashikin; Mohd Sham, Shaharuddin (STIKES Bhakti Husada Mulia Madiun, 2024)
This study aims to determine the health risk exposure of iron level in drinking water from gravity feed system among residents at Sungai Mas village, Sungai Lembing, Kuantan Pahang. A crosssectional research was carried out based on inclusion and exclusion criteria. The purposive sampling method was used to select respondents of Jakun and Semaq Beri tribe. This research had two parts;questionnaire,as well aswater sample collection and analysis. The iron level was determined using Hanna Instruments HI801-02 iris Visible Spectrophotometer, while pH level was determined using EUTECHC Cyberscan pH 310 Series Meter. Median and IQR of iron were 0.080 and 0.030 mg/L, respectively.There was no relationship between iron and pH levels of drinking water samples in the study area. There was no significant difference between iron levels in drinking water and the National Standard for Drinking Water Quality, and the value ranged between 0.030-0.550 mg/L. There was no health risk of iron exposure among respondents. The HQ was <1. Generally, drinking water containing iron had no adverse health effects. The iron in drinking water in this study was not influenced. So there are no carcinogenic effects on the community in Sungai Mas Village, Sungai Lembing.